Birth Defects Registries in the Genomics Era: Challenges and Opportunities for Developing Countries - Thong, Meow-Keong (Frontiers in Pediatrics, 2014)
Birth defects or congenital anomalies are one of the major causes of disability in developed and developing countries. Data on birth defects from population-based studies originating from developing countries are lacking. Increasingly there is a shift to genetic testing and genomics study of birth defects. However the translation from bench findings to bedside medicine has been muted. There is a need to address this imbalance where congenital anomalies remained the top aetiology for neonatal mortality in developing countries. To build capacity in low resource countries, there is a need for accurate collection and ascertainment of birth defects in developing countries. The systematic collection and analysis of data on major birth defects using birth defects registries (BDR) are an integral part of all clinical genetic services. Healthcare planners in developing countries must be aware of the advantages and limitations of BDRs. Despite the advent of the genomics era, BDRs are essential to the planning and developing care and prevention services at local and national levels, particularly in low resource or developing countries.